Analisis Perdagangan Foreign Exchange dengan Pendekatan Ichimoku Kinko Hyo - Langgeng Prayitno Utomo; Dadang Setiawan (Jurnal Bisnis dan Kewirausahaan, 2020)
This research aims to know how to analyse and determine foreign exchange trading using technical analysis using Ichimoku Kinko Hyo on the EUR-USD and USD-JPY currency pairs. This study uses a qualitative method which is a literature study using secondary data types, namely pictures taken from the back testing of the EUR-USD and USD-JPY currency pairs on the metatratder in January, February, and March. The study was conducted by applying a fundamental analysis that collects some information that is able to influence the economy and value of a currency, and technical analysis using Ichimoku Kinko Hyo which is able to show movement in the direction of a currency pair. The results of this study indicate that transaction decisions can be taken when both analyses show the same trend signal, whether price trends will move up or down.